Analisis Peran Pemerintah Daerah dalam Perlindungan Hak Anak (Studi Pelaksanaan Peraturan Daerah Nomor 3 Tahun 2013 tentang Penyelenggaraan Perlindungan Anak) - Nisarofa Istiqomah; Agus Riwanto (Res Publica: Jurnal Hukum Kebijakan Publik, 2022)
This study aims to determine and explain the role of the Kebumen Regency Regional Government in protecting children's rights and to analyze the implementation of Kebumen Regency Regional Regulation Number 3 of 2013 concerning the Implementation of Child Protection. The research method used is normative-empirical legal research with a statutory approach and conceptual approach. The types of data collected are secondary data and primary data, then the data is analyzed using qualitative methods. The results show that the implementation of child protection by the Community and Village Empowerment and Women's Empowerment and Child Protection Office of Kebumen Regency as a regional apparatus that assists the regional head in child protection affairs is in accordance with Kebumen Regency Regional Regulation Number 3 of 2013 concerning the Implementation of Child Protection. This is evidenced by the implementation of prevention efforts such as socialization, initiation of child-friendly schools, child-friendly health centers, women-friendly and child-caring villages (DRPPA), establishment of village child protection groups (KPAD/KPAK), establishment of district, sub-district and village child forums. For efforts to deal with victims as well as efforts to restore victims and social reintegration are carried out by the P2TP2A Kartika Team as the organizer of the function of protection and integrated services for victims of gender-based violence and children at the district level, the Kartika PPT Team which is the organizer of the function of protection and integrated services for children at the sub-district level, and the provision of a safe house as a temporary residence to provide protection to victims in accordance with the specified operational standards or fixed procedures. In addition, in the implementation of child protection in accordance with Kebumen Regency Regional Regulation No. 3 of 2013 concerning the Implementation of Child Protection, there are still obstacles that must be overcome.